Pelatihan Pemasaran UMKM Berbasis Digital Marketing Di Desa Pancur Jaya Kabupaten Bengkalis - Manaf, Muzaky Fadhlan; Siahaan, Titti Sulastri; Kholiza, Siti; Humairoh, Fitri; Sihombing, Mula Raja; Tanjung, Muhammad Reyhan; Permatasari, Nadia Indah; Sijabat, Bella Regita; Aurora, Shasi Kirani; Widiyanti, Heli (Jurnal Ilmiah Wahana Pendidikan, 2024)
MSME actors on average think that the marketing system for products or services through digital is difficult, complicated and they cannot do it. Whereas on the contrary, Digital Marketing actually has many sides that make it easy for everyone to do it. This Digital Marketing Training targets MSME actors so they are able to take advantage of digital devices in doing marketing. This fact is evident from the rise of online transactions through Marketplaces, online shops and even buying through Social Media. MSMEs Digital Marketing Training is a way that will accelerate the increase in the number of MSMEs to be able to take advantage of digital channels in marketing their products and increase MSME productivity and increase sales of local Indonesian products on the global market. The method used in community service activities is to use the marketing training method. Digital-based MSMEs in Pancur Jaya Village - Bengkalis Regency - Riau, which are easily mastered by MSME actors and can be operated by limited human resources. The training activity began with an opening by the Village Secretary, Pancur Jaya Village, then presentation of material by resource persons, then case discussions and discussions with participants regarding digital marketing-based MSMEs marketing training. The indicator of achievement can be seen how the participants understand the material presented and applied to their respective MSMEs.